2014
DOI: 10.1016/j.clbc.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography-Guided Breast-Conserving Surgery Is Superior to Palpation-Guided Surgery for Palpable Breast Cancer

Abstract: US-guided BCS is superior to palpation-guided excision in predicting the closest margins, obtaining clear surgical margins, and reducing re-operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 42 publications
(80 reference statements)
0
7
0
2
Order By: Relevance
“…Because clear margins are mandatory in breast-conserving surgery [3], surgeons face the dilemma of whether to generate a minimal defect within the breast while performing a precise tumor excision, or to make a wider excision and reduce the cosmetic results [4]. However, in some types of breast cancer, intraoperative assessment of margins is difficult to perform [5, 6]. Intraoperative frozen section analysis (FSA) is the standard microscopic method for margin assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Because clear margins are mandatory in breast-conserving surgery [3], surgeons face the dilemma of whether to generate a minimal defect within the breast while performing a precise tumor excision, or to make a wider excision and reduce the cosmetic results [4]. However, in some types of breast cancer, intraoperative assessment of margins is difficult to perform [5, 6]. Intraoperative frozen section analysis (FSA) is the standard microscopic method for margin assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Removed tissue volumes were higher in the palpation-guided cohort in most studies. In contrast, Eggemann et al reported higher specimen volumes in the IOUS group, but the difference was not statistically significant [26].…”
Section: Meta-analysis Of Rcts In Palpable Breast Cancermentioning
confidence: 85%
“…This study also evaluated the cosmetic outcome after ultrasoundguided lumpectomy, IOUS enabled the achievement of optimal resection volumes thanks to the less removal of healthy breast tissue, resulting in better aesthetic results and in greater patient satisfaction. Finally, Eggemann et al 23 obtained a 27.7 per cent rate of positive margins in the palpation-guided lumpectomy group compared with the 12.1 per cent one of the ultrasoundguided lumpectomy group.…”
Section: Discussionmentioning
confidence: 96%